Efek Pemberian Ekstrak Daun Gelagah (Saccharum spontaneum L.) terhadap Diabetes Induksi Aloksan pada Tikus Putih (Rattus Norvegicus) - Tiara Salsabilla Mendrofa; Asyrun Alkhairi Lubis (Jurnal Indah Sains dan Klinis, 2024)
Saccharum spontaneum L. (Family: Poaceae) is a tall perennial grass with deep roots and rhizomes, capable of growing up to 3-4 meters in height, and is commonly found along water bodies or roadsides. This plant is widely distributed throughout the tropical regions of Asia, Africa, America, and Australia. Saccharum spontaneum L. is a tall, erect, perennial grass with feathery inflorescences, often growing in swampy areas. Its leaves and stems contain lignin, carbohydrates, proteins, and amino acids, while its roots and lower stems contain starch and polyphenolic compounds. This study aims to evaluate the effect of Saccharum spontaneum L. leaves extract on blood glucose levels in male white rats (Rattus norvegicus) induced with alloxan. The leaves extract was obtained through maceration using 96% ethanol solvent. Phytochemical screening results indicated that the leaves of Saccharum spontaneum L. contain alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. The antidiabetic test was conducted using male Wistar rats. In this study, the Saccharum spontaneum L. leaves extract was administered in three different doses: group 4 received a dose of 100 mg/KgBW, group 5 received a dose of 200 mg/KgBW, and group 6 received a dose of 400 mg/KgBW. Additionally, there were control groups consisting of group 1 (normal), group 2 (negative control), and group 3 (positive control) which were given the drug glibenclamide 5 mg/60 kg. All doses were administered orally. Diabetes induction in the rats was performed using alloxan monohydrate at a dose of 100 mg/KgBW administered intraperitoneally. The results of the study showed that the greatest reduction in blood glucose levels occurred in group 6 with a dose of 400 mg/KgBW, which decreased blood glucose levels by 71.78% at the 180th minute. Group 5 showed a reduction of 55.80% and group 4 showed a reduction of 51.91% at the 180th minute. Group 3, which was given glibenclamide, showed a reduction in blood glucose levels of 71.14% at the 180th minute. These results indicate that the highest dose of Saccharum spontaneum L. leaves extract (400 mg/KgBW) had the most significant effect in lowering blood glucose levels in male Wistar rats induced with alloxan monohydrate